Mapping frontier research in the humanities - Emmeche, Claus; Pedersen, David Budtz; Stjernfelt, Frederik (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc., 2017)
"The classical sciences were organised around academic disciplines but knowledge production today is burgeoning and increasingly interdisciplinary, specialised; it is also distributed across a variety of societal sectors and increasingly involves interactions with extra-academic fields and transdisciplinary methods which focus on solving societal challenges. As a result, the notion of liberal arts and humanities within Western research universities is undergoing profound transformations. In Mapping Frontier Research in the Humanities, the contributors explore this transformative process. What are the implications, both for the modes of research and for intellectual leadership in higher education? Based on multidimensional methodologies for mapping knowledge diversity, the volume outlines reasons for optimism on the potentials as well as concerns regarding imbalances in the current hybrid university system. Drawing on a number of case studies and conceptual-empirical mappings of the humanities, the perceived divide between the classical humanities and 'post-academic' modes of research is critically discussed. Avoiding simple mechanical metrics, the contributors suggest a heuristic appreciation of different types of impact and styles of reasoning in the humanities. From this perspective, a more composite picture of human culture, language and history emerges from humanities research. It goes beyond the picture of rational agents, and situates human interaction in more complex landscapes of collective identities, networks, and constraints that open for new forms of intellectual leadership in the 21st century"--Provided by publish